Analysis of Proximate Level of Porang Tubers (Amorphophallus muerelli Blume) After Drying with Oven and Sun: Analisis Kadar Proksimat Umbi Porang (Amorphophallus muerelli Blume) Setelah Pengeringan dengan Oven dan Sinar Matahari - Ratih Kusuma Wardani; M.A. Hanny Ferry Fernanda (Akademi Farmasi Surabaya, 2023)
Porang tubers are one of the tubers that have special features compared to other tubers. Porang tubers contain glucomannan which has many health benefits. Glucomannan is a polysaccharide compound and contains high fiber. People have not been able to consume porang tubers directly because they contain high concentration of calcium oxalate. Soaking porang tubers in lime solution can help lower calcium oxalate levels. In addition to the content of glucomannan and calcium oxalate, proximate levels in porang tubers also need to be analyzed to determine the quality of processed porang tubers. In this study, an analysis of proximate levels in porang tubers was carried out before and after soaking in lime solution. The proximate levels of porang tubers before and after soaking with lime solution did not differ much. Porang tubers that have been dried for 6 days have a lower water content and higher carbohydrate content than tubers that have been dried for 4 days. Likewise, porang tubers that have been dried at 70 °C have a lower moisture content and higher carbohydrate content than tubers dried at 60 °C.